Clinical Efficacy Evaluation of Sirolimus in Congenital Hyperinsulinism - Somayyeh Hashemian; Reza Jafarzadeh Esfehani; Siroos Karimdadi; Rahim Vakili; Daniel Zamanfar; Amirhossein Sahebkar (International Journal of Endocrinology)
Background. Congenital hyperinsulinism (CHI) is a rare and life-threatening genetic disorder. Sirolimus as a mammalian target of rapamycin inhibitor may be helpful in patients with CHI who do not respond well to other treatments including diazoxide and octreotide. However, the safety and efficacy of this therapy are still unclear. This study aimed to evaluate the potential therapeutic effects of sirolimus in CHI patients with mutations in the ABCC8 and KCNJ11 genes. Methods. During the period of this follow-up study, every child with a confirmed diagnosis of unresponsive CHI underwent genetic evaluation. Among those who had positive genetic testing, six families agreed to participate in this study. The participants were evaluated for ABCC8, KCNJ11, or HNF4α gene mutations by polymerase chain reaction (PCR) sequencing. The participants who were unresponsive to diazoxide and octreotide therapy received 0.5 mg/m2/d of sirolimus, and the dose was gradually increased until a serum concentration of 5–15 ng/ml was achieved. Then, the participants were followed up for any possible complications. Results. Among the study participants, only one neonate was completely free of hypoglycemia after one year of follow-up, whereas three others experienced a partial reduction in hypoglycemic episodes over six months. One neonate underwent pancreatectomy despite receiving sirolimus. The oldest participant with a mutation in the ABCC8 gene responded well to sirolimus therapy after surgery and remained asymptomatic for 18 months. Conclusion. This study suggested that sirolimus therapy needs further evaluation to determine which patients will benefit the most. The genetic basis of CHI may have possible implications for determining the patient’s response.